Temperature Response in Acute Cerebrovascular Accidents - D. V. Sadchikov; S. N. Kotov; T. V. Rodionova (Общая реаниматология, 2014)
Objective: to clarify the causes and changes of body temperature in relation to the type of stroke and the presence or absence of pyoinflammatory complications.Subjects and methods. The case histories were retrospectively analyzed in 211 survivors and deceased patients with acute cerebrovascular accident at the age of 38—87 years. In the patients from different groups and subgroups, changes in their temperature were assessed from its curves during their hospital stay. Indicators, such as initiation of hyperthermia (hours), duration of hyperthermia (days) and unrelieved hyperthermia (hours), were estimated. The pattern and number of pyoinflammatory complications in each patient were taken into account.Results. The paper deals with the retrospective analysis of a temperature response in the survivors and deceased patients with myocardial infarction and intracerebral hemorrhage. It shows body temperature changes in relation to the type of stroke and the presence or absence of pyoinflammatory complications, such as pneumonia, meningitis, purulent tracheobronchitis, etc. The main causes of hyperthermia in stroke were elucidated.Conclusion. Hyperthermia affects negatively the outcome of stroke and increases the length of hospital stay regardless of the type of stroke. In patients with acute cerebrovascular accident, the causes of hyperthermia are a focus of brain injury, blood in the cerebrospinal fluid system, and pyoinflammatory complications.